(Un) Just Deserts: Examining Resource Deserts and the Continued Significance of Racism on Health in the Urban South. Issue 4 (October 2022) - Satcher, Lacee A.
With concepts like structural racism and social determinants of health currently trending in both academic and public discourse, examining the health consequences of legacies of racism in the built environment is increasingly timely. Resource scarcity in neighborhoods and the emergence of resource deserts in urban cities are critical sources of urban social inequality. As research shows how the sociodemographic makeup of neighborhoods can predict resident access to important material resources like grocery stores, pharmacies, and parks, exploring how this lack of access might impact health is imperative. Employing an environmental justice framework, this study brings together scholarship on environmental racism and stress theory to explore the impacts of spatial inequality on health at the neighborhood level. Using public-use data from the American Community Survey (ACS), Centers for Disease Control and Prevention (CDC), the National Provider Identifier (NPI) registry, and local and state government sources, the author examines the influence of co-occurring resource scarcity (i.e., multiply-deserted areas [MDAs]) on health in neighborhoods across urban cities in the American South. Results indicate that MDAs have higher prevalence of physical inactivity, asthma, diabetes, and obesity compared to neighborhoods with low or no resource scarcity. In addition, across MDAs, neighborhoods that are predominantly Black have higher prevalence of physical inactivity, asthma, diabetes, and obesity relative to nonpredominantly Black neighborhoods. Results also suggest that higher income MDAs have lower obesity prevalence compared with low-income MDAs. Findings contribute to a growing area of literature connecting and examining the structural racism-health connection.